Desperately Seeking Science - Francis J. Mootz III (Washington University Law Quarterly, 1995)
In this Article I offer a lawyer's view of what law and linguistics interdisciplinary studies might mean for legal practice, as well as a legal theorist's view of what importance they may hold for jurisprudence. I do not pretend to have more than cursory knowledge about linguistics, and so my remarks about what linguistics scholars might gain from an interdisciplinary exchange necessarily will be brief and general.
Keywords: Linguistics; Science; Jurisprudence